2021
DOI: 10.1007/s13369-021-06005-8
|View full text |Cite
|
Sign up to set email alerts
|

Reservoir Formation Damage; Reasons and Mitigation: A Case Study of the Cambrian–Ordovician Nubian ‘C’ Sandstone Gas and Oil Reservoir from the Gulf of Suez Rift Basin

Abstract: Reservoir formation damage is a major problem that the oil and gas industry has to mitigate in order to maintain the oil and gas supply. A case study is presented that identifies the impacts of formation damage and their causes in the Nubian ‘C’ hydrocarbon reservoir within Sidki field located in the Southern Gulf of Suez, Egypt. In addition, a formation damage mitigation program was designed and implemented involving an effective stimulation treatment for each well experiencing reservoir damage. The data avai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(6 citation statements)
references
References 77 publications
(83 reference statements)
0
6
0
Order By: Relevance
“…As evidenced by geophysical and borehole data, the basin is filled with more than a 5-km-thick sedimentary sequence ranging from the Precambrian to the Quaternary (Metwalli et al, 1981;Metwalli et al, 1982;El-Hattab, 1982;Montenat et al, 1988;EGPC, 1996;Radwan, 2022b), which is punctuated by several unconformities of different magnitudes and ages (Figure 3). The studied area of El Morgan oil field is situated in the south central offshore area of the rift basin, where numerous hydrocarbon plays are present (Figure 3) (Alsharhan and Salah, 1995;EGPC, 1996;Bosworth and McClay, 2001;Barakat et al, 2002;Youssef et al, 2002;Alsharhan, 2003;Radwan, 2014;Attia et al, 2015;Abudeif et al, 2016a;El Ayouty, 2017;Abudeif et al, 2018;Radwan, 2018;Radwan et al, 2019a;Radwan et al, 2019b;Radwan et al, 2019c;Radwan et al, 2020a;Radwan et al, 2020b;Radwan et al, 2020c;Radwan et al, 2021c;Radwan et al, 2021d;Radwan et al, 2021e;Ali et al, 2022). El Morgan field is located on the southwest coast of the Sinai Peninsula, covering an area of roughly 46 km 2 (Bentley and Biller, 1990;Radwan, 2014;Attia et al, 2015).…”
Section: Geologic Setting and Lithostratigraphymentioning
confidence: 99%
See 1 more Smart Citation
“…As evidenced by geophysical and borehole data, the basin is filled with more than a 5-km-thick sedimentary sequence ranging from the Precambrian to the Quaternary (Metwalli et al, 1981;Metwalli et al, 1982;El-Hattab, 1982;Montenat et al, 1988;EGPC, 1996;Radwan, 2022b), which is punctuated by several unconformities of different magnitudes and ages (Figure 3). The studied area of El Morgan oil field is situated in the south central offshore area of the rift basin, where numerous hydrocarbon plays are present (Figure 3) (Alsharhan and Salah, 1995;EGPC, 1996;Bosworth and McClay, 2001;Barakat et al, 2002;Youssef et al, 2002;Alsharhan, 2003;Radwan, 2014;Attia et al, 2015;Abudeif et al, 2016a;El Ayouty, 2017;Abudeif et al, 2018;Radwan, 2018;Radwan et al, 2019a;Radwan et al, 2019b;Radwan et al, 2019c;Radwan et al, 2020a;Radwan et al, 2020b;Radwan et al, 2020c;Radwan et al, 2021c;Radwan et al, 2021d;Radwan et al, 2021e;Ali et al, 2022). El Morgan field is located on the southwest coast of the Sinai Peninsula, covering an area of roughly 46 km 2 (Bentley and Biller, 1990;Radwan, 2014;Attia et al, 2015).…”
Section: Geologic Setting and Lithostratigraphymentioning
confidence: 99%
“…El Morgan field is classified as the biggest giant oil field in Egypt with more than 1.5 BBO reserves. The stratigraphic sequence of El Morgan oil field is classified into three main depositional mega sequences, namely pre-rift, syn-rift, and post-rift (Brown, 1980;Attia et al, 2015;Abudeif et al, 2016a;Abudeif et al, 2016b;Radwan et al, 2019b;Radwan et al, 2019c;Radwan, 2021a;Radwan, 2021b;Radwan, 2021c;Radwan et al, 2021c;Radwan et al, 2021d;Radwan et al, 2021e). The deposition of sediments in the study area took place in different depositional environments (EGPC, 1996).…”
Section: Geologic Setting and Lithostratigraphymentioning
confidence: 99%
“…The damage of such reservoir formations can be generated by multiple sources [ 13 ]. The mechanisms of reservoir damage can be classified into four types: mechanical; chemical; biological; and thermal processes [ 14 , 15 , 16 ]. Studies and explorations have indicated that the subsalt carbonate formations in the Middle East have strong heterogeneity.…”
Section: Introductionmentioning
confidence: 99%
“…There are minerals such as halite, clay minerals and iron oxides, found within the components of sandstone, where these minerals are subjected to change when interacting with various damage factors [13] [14]. Wet and dry cycles cause complex mechanical damage in particular when salts are found in the pores of the stone; because it is characterized by high porosity, so it has ability to absorb moisture from air or ground, thus facilitating penetration of salts spray into its components causing physiochemical damage, especially when the dissolved salts turn to different crystalline sizes, causing cracks in internal structure of the stone [15], because sodium chloride salt is hygroscopic and tends to absorb water, the presence of water causes the salt crystal to expand, creating pressures and tensions inside the stone that cause disintegration of the binding material of sandstone; the stone's containment of iron compounds makes it vulnerable to oxidation, such as the transformation of ferrous compounds into ferric compounds, where iron compounds change the color of the stone, and ferric compounds increase in size when they acquire water of crystallization, causing stresses in the stone's structure, which accelerates the process of damage, and this phenomenon is known stone disease [16] [17]. Most sandstone has clays in the cement that binds the grains together.…”
Section: Introductionmentioning
confidence: 99%